Cells and Mediators of Inflammation in Acute Pancreatitis - Kumar, Ramesh; Bhatia, Madhav (Clinical Anti-Inflammatory & Anti-Allergy Drugs (Discontinued), 2014)
Acute pancreatitis (AP) is an acute inflammatory process of the pancreas which involves a complex cascade of events initializing in pancreatic acinar cells. This, in turn leads to an inflammatory response, which results in the pathology of acute pancreatitis. In this review, we describe the role of different cell types and inflammatory mediators in the pathogenesis of acute pancreatitis.
Keywords: transcription factors